Life cycle of Agrotis malefida (Lepidoptera: Noctuidae): a diapausing cutworm - Specht,Alexandre (2013)
This study describes the life cycle of Agrotis malefida Guenée, 1852 (Noctuidae: Noctuinae) under laboratory conditions. The insects were reared in a controlled environment (25 ± 1ºC, 70 ± 10% RH and 14 hours photo phase) and observed daily. The larvae were fed Greene's artificial diet and adults were offered a 10% sucrose solution. The viability and duration of immature stages were assessed. The experiment initiated with 2,410 eggs. Larvae were isolated shortly after hatching. Longevity, pre-, post- and oviposition, fecundity and fertility of 13 adult couples were also evaluated. The viability of eggs, larvae, pupae and pre-pupae was 96.72, 91.25, 78.37 and 95.26%, respectively. The average duration of egg, larva, pre-pupa, pupa and adult was 7.93, 54.26, 61.61, 37.43 and 12.85 days, respectively. The immature stage of A. malefida lasted an average of 161.29 days, ranging from 102 to 227 days. The life cycle of A. malefida is much longer than that of congeners. The mean fecundity was 1,696.77 eggs and fertility 1,641.15 larvae per female. Under the conditions in which the study was conducted, the biotic potential of A. malefida was of 606,666.59 individuals/female/year. The results also indicated that this species goes through larval (pre-pupae) and pupal diapause.